(untitled) (Research Nepal Journal of Development Studies, 2020)
Gandhian Model of Community Development (GMCD) is a sustainable development model for governments in the central, provincial, and local levels of democratic federal countries in the world by the scientific analysis of Gandhian ideology in a specified community. Community Development is a method, a strategy, and a campaign to uplift human life settlements and to solve the community problems from a simple local perspective. The human settlement with local communal acceptance, local norms, and values, environmental protection, help and cooperation, trusteeship, health, education, sanitation, training, transportation, marketing, etc. are the major components of the Gandhian Model of Community Development. The global acceptance with local initiation, norms, knowledge and practices in the positive changes on human life is Gandhian Community Development. It is the core ideological view of the great leader of south Asia-Mahatma Gandhi. Mahatma Gandhi is also pronounced as second Buddha of the world. The main objective of the study is to develop a Gandhian Model of Community Development with the incorporation of thoughts and ideologies of Mahatma Gandhi. The study is the collection of Gandhian ideology with a programmatic model for the future development of the human being specified within the boundary with the specified indicators of the Gandhian Model of Community Development. It is a hermeneutic and historical interpretation of three universal truths- Generation, Operation, and Destruction for the liberation of human beings from a sustainable development strategy guided by Mahatma Gandhi. His ideas are herminuted in contemporary sustainable community development. In conclusion, the Gandhian Model of Community development is a model having Balance Sheet of Production and Consumption within the specified municipality and Gandhian Development Indicators for human liberation or development toward ultimate freedom.